Let be the set of the first natural numbers.
Let be a function defined by
Determine the natural number for which the sum
If you believe no such exists, submit your answer as .
Details and Assumptions:
denotes the set of all natural numbers, which are .
sometimes includes , but don't for the purposes of this problem
is the power set of the set , or the set of all subsets of , including itself.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let f : N → N be a function defined by
f ( k ) = C ∈ P ( S k ) ∑ p ( C ) 1
Let's start by looking at the values of f ( k ) for the first few values of k
S 1 = { 1 } S 2 = { 1 , 2 } S 3 = { 1 , 2 , 3 } ⇒ f ( 1 ) = C = ∅ 1 1 + C = { 1 } 1 1 = 2 ⇒ f ( 2 ) = C = ∅ 1 1 + C = { 1 } 1 1 + C = { 2 } 2 1 + C = { 1 , 2 } 2 1 = 3 ⇒ f ( 3 ) = C = ∅ 1 1 + C = { 1 } 1 1 + C = { 2 } 2 1 + C = { 1 , 2 } 2 1 + C = { 3 } 3 1 + C = { 1 , 3 } 3 1 + C = { 2 , 3 } 6 1 + C = { 1 , 2 , 3 } 6 1 = 4
From this, it appears that f ( k ) = k + 1 for these first few values of k , so let's generalize this
Claim:
f ( k ) = k + 1 for all k ∈ N
Proof:
To show this, lets look at how to construct P ( S k ) from P ( S k − 1 ) .
We know that every set in P ( S k − 1 ) will also be in P ( S k ) , since C ∈ P ( S k − 1 ) ⇒ C ⊆ S k − 1 ⊂ S k ⇒ C ⊂ S k ⇒ C ∈ P ( S k ) , Hence we can express the function f ( k ) as
f ( k ) = C ∈ P ( S k ) ∑ p ( C ) 1 = C ∈ P ( S k − 1 ) ∑ p ( C ) 1 + C ∈ P ( S k ) ∧ C ∈ / P ( S k − 1 ) ∑ p ( C ) 1 = f ( k − 1 ) + C ∈ P ( S k ) \ P ( S k − 1 ) ∑ p ( C ) 1
It isn't too difficult to see that C ∈ P ( S k ) \ P ( S k − 1 ) only if k ∈ C , since if k ∈ / C , we have that C ⊂ S k ⇒ C ⊂ S k − 1 ∪ { k } ⇒ C ⊆ S k − 1 ⇒ C ∈ P ( S k − 1 ) , and so if k ∈ / C and C ⊂ S k , we must have that C ∈ / P ( S k ) \ P ( S k − 1 ) .
This means that the remaining sum is over all subsets of S k which contain k . But these sets are just all of the sets of the form C = D ∪ { k } : D ∈ P ( S k − 1 ) Hence, the remaining sum becomes
C ∈ P ( S k ) \ P ( S k − 1 ) ∑ p ( C ) 1 = D ∈ P ( S k − 1 ) ∑ p ( D ∪ { k } ) 1 = D ∈ P ( S k − 1 ) ∑ [ p ( D ) 1 × k 1 ] = k 1 ⎣ ⎡ D ∈ P ( S k − 1 ) ∑ p ( D ) 1 ⎦ ⎤ = k 1 f ( k − 1 )
And so, we can complete our expression for f ( k ) as a recursive formula in terms of f ( k − 1 ) as
f ( k ) = f ( k − 1 ) + C ∈ P ( S k ) \ P ( S k − 1 ) ∑ p ( C ) 1 = f ( k − 1 ) + k 1 f ( k − 1 ) = k k + 1 f ( k − 1 )
Proceed by induction:
f ( n ) = n + 1 is true for n = 1 , as we saw from testing the first few k .
Assume f ( j ) = j + 1 for some j ∈ N . Then f ( j + 1 ) = j + 1 ( j + 1 ) + 1 f ( j ) = j + 1 ( j + 2 ) ( j + 1 ) = j + 2 . This is our assumed expression for j + 1 , which proves the inductive step.
And so we conclude that f ( n ) = n + 1 for all n ∈ N . This means that f ( 2 0 1 7 ) = 2 0 1 8 , and that 2 0 1 7 is our answer.